From the centralized national collection policy towards a decentralized collection management and resource sharing co-operation – Finnish experiences. Issue 1 (13th January 2014) - Muhonen, Ari; Saarti, Jarmo; Vattulainen, Pentti
Abstract : Purpose: – Finland had a legislation-based centralized collection policy until the mid-1990s. The main components were national resource centers (selected higher education libraries) and provincial libraries (selected public libraries). This paradigm changed during the recession of the 1990s when new public management ideologies were adopted by the government. This ended the centralized model and a new policy favoring a decentralized collection management which demanded resource sharing. The models designated for the print-only age became obsolete also when the digital dissemination of especially scientific documents began to be the norm. The Finnish libraries have started to implement a new strategy consisting of different elements including a new model of library automation systems, the National Repository which is the hub for the resource sharing of print materials, digitization projects (to be especially implemented by the National Library) and with new policies defining the roles and responsibilities of each of the libraries involved. This article aims to describe the history of the Finnish centralized collection policy, its shift to the modern management of the collection as well as the philosophy and tools used in this work. Design/methodology/approach: – The paper describes the evolution of the Finnish national collection policy and its main trends. Findings: – The National Repository Library has enabled Finnish university libraries to focus their collection policies and to make savings in the cost of premises. A new business model for the digital era is needed for document sharing between libraries. Research limitations/implications: – The paper is based on Finnish experiences. Practical implications: – Models for national and international collection and preservation policies are presented. Originality/value: – The paper provides proposals for the building of global division of work in the long-tail management of documents.